Relationship between problematic smartphone use and academic self-efficacy: a correlational study on gen Z students - Sholihah, Maratus; Nisa, Athia Tamyizatun (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Excessive smartphone use can lead to problematic smartphone use in students, especially Gen Z students. Problematic smartphone use can have physical, cognitive, and affective impacts on users, including affecting their academic self-efficacy. This study aims to determine the relationship between problematic smartphone use and academic self-efficacy in Gen Z students. The respondents of this study were Islamic Guidance and Counseling students at Raden Mas Said State Islamic University Surakarta. The sampling technique used was proportional stratified random sampling (N = 265 students). Data collection was carried out using the Smartphone Application-Based Addiction Scale (SABAS) and The Academic Self-Efficacy Scale (TASES) on Google Form via a link distributed via WhatsApp. The results of the Spearman rank correlation analysis found no relationship between the two research variables (r = -0.085, p> 0.05). However, further analysis found that there was a relationship between problematic smartphone use and academic self-efficacy in male students.